2003
DOI: 10.1080/0026897031000155625
|View full text |Cite
|
Sign up to set email alerts
|

QC-DMRG study of the ionic-neutral curve crossing of LiF

Abstract: We have studied the ionic-neutral curve crossing between the two lowest 1 Σ + states of LiF in order to demonstrate the efficiency of the quantum chemistry version of the density matrix renormalization group method (QC-DMRG). We show that QC-DMRG is capable to calculate the ground and several low-lying excited state energies within the error margin set up in advance of the calculation, while with standard quantum chemical methods it is difficult to obtain a good approximation to Full CI property values at the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
153
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(154 citation statements)
references
References 24 publications
0
153
0
1
Order By: Relevance
“…[6][7][8][9][10][11] After early attempts to use the DMRG as a full configuration interaction (FCI) method for small molecules, 7,10,[12][13][14] it was recognised that DMRG is best used to describe non-dynamical correlation in active spaces. The DMRG algorithm exhibits a cost scaling of O(k 3 …”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11] After early attempts to use the DMRG as a full configuration interaction (FCI) method for small molecules, 7,10,[12][13][14] it was recognised that DMRG is best used to describe non-dynamical correlation in active spaces. The DMRG algorithm exhibits a cost scaling of O(k 3 …”
Section: Introductionmentioning
confidence: 99%
“…Different attempts to avoid the length of configurational expansions are the density matrix renormalization group method, [72][73][74][75] the variational density matrix method, 76,77 and the iterative configuration interaction method. 78 In order to make contact with physical reality, all orbitalconfiguration-based wavefunctions and/or energies must be extrapolated to the "complete basis set ͑CBS͒ limit."…”
Section: Introductionmentioning
confidence: 99%
“…[163] the symmetric reverse Cuthill-Mckee reordering, which attempts to make t i j as band-diagonal as possible, was shown to lead to faster convergence in m and the number of finite-system sweeps as compared to Hartree-Fock ordering. Improvement was also obtained by optimizing the ordering using the Fock term which contains contributions from both t i j and parts of the interaction V i jkl [164]. Ideas from Quantum Information Theory also seem to be important: Legeza and Sólyom [109] have shown that the profile along the chain of the entanglement entropy between single sites and the rest of the system is important.…”
Section: Dynamicsmentioning
confidence: 99%